Pengaruh Tingkat Pendidikan Terhadap Tingkat Kesejahteraan Masyarakat di Kabupaten Bantul - Nurwahyudi, Muhammad Robi (Jurnal Solusi, 2020)
Education is one of the keys someone in improve their life.Education someone able to perform social mobility, like a from those can do the down to the middle group up since schooling ditempuhnya have of that he get job. But, conditions on the ground now cannot be entirely describe the state of society.Research aims to understand what factors melatar such recognition of the importance of educated at Kabupaten Bantul and to know the education level the end of concerning the economic welfare in kabupaten Bantul.This research used the quantitative type. This research used the quantitative kind of stressing the analysis on data-data numerical (figures) mixed with statistika method. To know relations , used statistical tests using the correlation product moment. The result showed that is no link between the level of education ( TP ) for the welfare of (Ks)